Still a wearable that enables controlled fidgeting and effective time management for students aged 8-12 years old diagnosed with AD/HD - Santos, Joaquin Iñigo M.; Constantino, Nina Elisa B. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2018)
AD/HD is not a disease, but a disorder. Unlike a disease, there is no cure for mental disorders such AD/HD. People diagnosed with the disorder must learn to cope and learn to live with it. Due to the fact that most children are diagnosed with AD/HD, from a young-age they must learn to live life with their disorder. The disorder can be diagnosed into three types: hyperactive-impulsive, inattentive, or a combination of both. Majority of children are diagnosed with both types, so they manifest both behaviors of the disorder. Given the different manifestations and behaviors of AD/H, learning and academic life can be quite hard for students diagnosed with AD/HD. Some of the many factors they have to face on a day to day basis is concentration and being organized. Still is a wearable device that will aid students diagnosed with AD/HD cope with there disorder. The device will allow the users to discretely fidget in a controlled fashion as not to distract the users themselves and/or others around them. Effective time management is also promoted via the different sensations or cues of the passing of time All these features conveniently packaged in a wearable device that appeals to children.
Thesis (Bachelor of Fine Arts in Industrial Design)--University of the Philippines Diliman
Bibliography.
Keywords: Attention-deficit hyperactivity disorder